Evaluation of Potential Sites for Solar Powered Irrigation System in Gilgit-Baltistan for Sustainable Agriculture - Arshad Ashraf; Muhammad Bilal Iqbal; Imran Ahmad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
The depletion of glaciers and frequent occurrence of glacial floods and landslide hazards typically affect the irrigation channels, resulting in disruption of water supplies for irrigation and domestic use in the Upper Indus Basin (UIB). The cultivated and arable land requires sustainable and alternative irrigation sources, such as using river/stream water through solar-powered irrigation system (SPIS), to ensure food security in the region. An effort has been made to assess the potential of SPIS in Gilgit-Baltistan (GB) province, lying in the UIB of Pakistan, based on the climate and topographic indexing approach. The SPIS potential was found to be high over 2153 km² and moderate over 3786 km² (collectively over 5939 km²) of the GB based on the slope-aspect (SLA) suitability. The high and moderate SLA suitability areas for SPIS were observed collectively over 22.9% of the Diamer, 16.9% of the Gilgit, and 8.8% of the Astore District. The SLA suitability was observed high over 11.2% and moderate over 19.2% area of the cropping zone below 3500 m elevation in the GB. The SPIS system may be adopted through coupling with some storage facility (water tanks, ponds, or reservoirs) and high efficient irrigation system (drip, sprinkler, and bubbler) for raising high value crops and multipurpose plant species, while reducing water consumption, fuel and labor cost. Integrated water resources management strategies need to be developed and implemented to cultivate unused lands in the valleys to ensure food security and economic development in the region in future.